2017
DOI: 10.1007/s12079-017-0377-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pancreatic β-cell function and mass dynamics by prostaglandin signaling

Abstract: Prostaglandins (PGs) are signaling lipids derived from arachidonic acid (AA), which is metabolized by cyclooxygenase (COX)-1 or 2 and class-specific synthases to generate PGD, PGE, PGF, PGI (prostacyclin), and thromboxane A. PGs signal through G-protein coupled receptors (GPCRs) and are important modulators of an array of physiological functions, including systemic inflammation and insulin secretion from pancreatic islets. The role of PGs in β-cell function has been an active area of interest, beginning in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 94 publications
1
34
2
3
Order By: Relevance
“…The presence of inflammatory receptors like PGTER4 may couple localized pancreatic or more global responses to islet output of insulin. Systemic delivery of high levels of PGE2 appear to lower insulin secretion 39,40 , but the selective effects on  cell proliferation or survival versus direct effects on insulin secretion are not fully separated. The broader context of activating PGE2 levels in pancreatic islets may cause a variety of effects.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of inflammatory receptors like PGTER4 may couple localized pancreatic or more global responses to islet output of insulin. Systemic delivery of high levels of PGE2 appear to lower insulin secretion 39,40 , but the selective effects on  cell proliferation or survival versus direct effects on insulin secretion are not fully separated. The broader context of activating PGE2 levels in pancreatic islets may cause a variety of effects.…”
Section: Discussionmentioning
confidence: 99%
“…COX 1 and 2), which catalyze the intermediate conversion of PGH2 to PGE2. Elevated islet expression of specific PGE2 synthetic enzymes and/or islet PGE2 excretion has been observed in islets from T2D animals and humans (2,5,6,8,9,20,37). Yet, in this study, PGE2 production was not enhanced in HGOB islets above the levels observed in either lean or NGOB.…”
Section: Discussionmentioning
confidence: 99%
“…ПЗ має дві частини: екзокринну, що продукує широкий спектр травних ферментів, і ендокринну, яка формує 1-3 % маси залози і є джерелом панкреатичних гормонів [22,27]. Ендокринна і екзокринна частини ПЗ розвиваються з одного ембрі-онального джерела [3,10] і тісно пов'язані анатомічно, однак при цьому часто ці дві частини вивчаються окремо один від одного [2,5,14,17,27].…”
unclassified
“…Протягом 4 місяців у щурів усіх груп було зроблено аналіз змін маси тіла. 4-місячних тварин декапітували, збирали ПЗ для гістологічного та імуногістохімічного дослідження [5,18].…”
unclassified
See 1 more Smart Citation